2016
DOI: 10.3389/fmicb.2016.01710
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipids Produced by Indigenous Acinetobacter junii from Petroleum Reservoir and its Potential in Enhanced Oil Recovery

Abstract: Biosurfactant producers are crucial for incremental oil production in microbial enhanced oil recovery (MEOR) processes. The isolation of biosurfactant-producing bacteria from oil reservoirs is important because they are considered suitable for the extreme conditions of the reservoir. In this work, a novel biosurfactant-producing strain Acinetobacter junii BD was isolated from a reservoir to reduce surface tension and emulsify crude oil. The biosurfactants produced by the strain were purified and then identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 61 publications
1
10
0
2
Order By: Relevance
“…The ability of recovering oil from oil‐saturated core was also observed, and it was observed that 28% additional residual oil was displaced after water flooding . Rhamnolipids synthesized by A. junii BD has great potential in microbial enhanced oil recovery (MEOR) because of its properties like interfacial surface reduction, wettability, and alteration . Ohadi et al studied the properties of biosurfactant produced by A. junii B6 and concluded that this biosurfactant has potential application in enhanced oil recovery process .…”
Section: Applications Of Biosurfactants Produced By Acinetobacter Sppmentioning
confidence: 99%
“…The ability of recovering oil from oil‐saturated core was also observed, and it was observed that 28% additional residual oil was displaced after water flooding . Rhamnolipids synthesized by A. junii BD has great potential in microbial enhanced oil recovery (MEOR) because of its properties like interfacial surface reduction, wettability, and alteration . Ohadi et al studied the properties of biosurfactant produced by A. junii B6 and concluded that this biosurfactant has potential application in enhanced oil recovery process .…”
Section: Applications Of Biosurfactants Produced By Acinetobacter Sppmentioning
confidence: 99%
“…The oil-production wells were dominated by Gammaproteobacteria (Pseudomonadaceae), Betaproteobacteria (Rhodocyclaceae, Hydrogenophilaceae), Epsilonproteobacteria (Campylobacteraceae), and Deltaproteobacteria (Geobacteraceae), including facultative anaerobic dominant genera Pseudomonas , Thauera , Hydrogenophaga , Acinetobacter , Atribacteria , Arcobacter , Acetobacterium , and Geobacter . Many strains of Pseudomonas and Acinetobacter are capable of utilizing hydrocarbons and producing biosurfactants (6, 48, 49). Geobacter plays an important role in electron exchange by direct interspecies electron transfer (1).…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics make them extraordinary valuable for industrial and environmental applications in areas such as petroleum, pharmaceutical, cosmetics, and food industries [1]. Peculiarly, bioemulsifiers were widely studied for potential usages in the petroleum industry, such as microbial enhanced oil recovery (MEOR) [8, 9] and bioremediation of contaminated soil or other environmental pollution [10]. Despite their potential advantages, some obstacles impede the practical applications of bioemulsifiers, including low yields and high purification costs.…”
Section: Introductionmentioning
confidence: 99%